Lignin syngas bioconversion by Butyribacterium methylotrophicum: advancing towards an integrated biorefinery - Pacheco, Marta (2021)
ABSTRACT: Hybrid bio-thermochemical based technologies have the potential to ensure greater feedstock flexibility for the production of bioenergy and bioproducts. This study focused on the bioconversion of syngas produced from low grade technical lignin to C-2-/C-4-carboxylic acids by Butyribacterium methylotrophicum. The effects of pH, medium supplementation and the use of crude syngas were analyzed. At pH 6.0, B. methylotrophicum consumed CO, CO2 and H-2 simultaneously up to 87 mol% of carbon fixation, and the supplementation of the medium with acetate increased the production of butyrate by 6.3 times. In long-term bioreactor experiments, B. methylotrophicum produced 38.3 and 51.1 mM acetic acid and 0.7 and 2.0 mM butyric acid from synthetic and lignin syngas, respectively. Carbon fixation reached 83 and 88 mol%, respectively. The lignin syngas conversion rate decreased from 13.3 to 0.9 NmL/h throughout the assay. The appearance of a grayish pellet and cell aggregates after approximately 220 h was indicative of tar deposition. Nevertheless, the stressed cells remained metabolically active and maintained acetate and butyrate production from lignin syngas. The challenge that impurities represent in the bioconversion of crude syngas has a direct impact on syngas cleaning requirements and operation costs, supporting the pursuit for more robust and versatile acetogens.